2009
DOI: 10.5194/acp-9-9647-2009
|View full text |Cite
|
Sign up to set email alerts
|

Hydration and dehydration at the tropical tropopause

Abstract: Abstract. High-resolution water measurements from three tropical airborne missions in Northern Australia, Southern Brazil and West Africa in different seasons are analysed to study the transport and transformation of water in the tropical tropopause layer (TTL) and its impact on the stratosphere. The mean profiles are quite different according to the season and location of the campaigns, with lowest mixing ratios below 2 ppmv at the cold point tropopause during the Australian mission in November/December and h… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
96
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 106 publications
(110 citation statements)
references
References 50 publications
11
96
0
1
Order By: Relevance
“…These processes include deep convection, cloud microphysics and transport. Additionally, extratropical dynamical processes like mixing, crosstropopause exchange and convective injections into the lower stratosphere (e.g., Schiller et al, 2009;Ravishankara, 2012;Ploeger et al, 2013) may affect the quality of ECMWF (re)analyses water vapor in the extratropical lower stratosphere. Dyroff et al (2014) indicated an insufficient model resolution of small-scale intrusions of air masses in the UTLS, and an influence of numerical diffusion associated with the advection scheme in the vicinity of sharp humidity gradients at the tropopause may play a role.…”
Section: Summary and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These processes include deep convection, cloud microphysics and transport. Additionally, extratropical dynamical processes like mixing, crosstropopause exchange and convective injections into the lower stratosphere (e.g., Schiller et al, 2009;Ravishankara, 2012;Ploeger et al, 2013) may affect the quality of ECMWF (re)analyses water vapor in the extratropical lower stratosphere. Dyroff et al (2014) indicated an insufficient model resolution of small-scale intrusions of air masses in the UTLS, and an influence of numerical diffusion associated with the advection scheme in the vicinity of sharp humidity gradients at the tropopause may play a role.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…Polar campaigns such as RECON-CILE2010 were aimed at a better understanding of polar vortex dynamics and chemical reactions (von Hobe et al, 2013). Other campaigns, such as the eight SPURT campaigns over 2 years, were intended to observe seasonal differences of various trace gases in the midlatitude tropopause region , and tropical campaigns such as TROC-CINOX2005 investigated the impact of tropical deep convection on the distribution and the sources of trace gases, cloud and aerosol particles in the UTLS (Flentje et al, 2007;Schiller et al, 2009). …”
Section: Fish-based Water Vapor Climatologymentioning
confidence: 99%
See 1 more Smart Citation
“…10,11 The air enters the stratosphere through the cold tropical tropopause and is ''freeze dried'' down to a few ppmv of water. 12 After crossing the tropical tropopause, the air ascends into the upper stratosphere and finally descends at polar latitudes within a typical transit time of 4 to 6 years from the Earth's surface to the upper stratosphere (see Fig. 1).…”
Section: Possible Impact Of a Future Hydrogen Economy On The Stratospmentioning
confidence: 99%
“…FISH (Fast In situ Stratospheric Hygrometer) is a closed cell Lyman-α photofragment fluorescence hygrometer which has been operated on various research aircraft for more than 20 years (Meyer et al, 2015;Schiller et al, 2009). The operating principle of the instrument is described in detail by Zöger et al (1999).…”
Section: Fishmentioning
confidence: 99%